Transcriptome analysis reveals the oxidative stress response in Saccharomyces cerevisiae1. Issue 29 (2nd April 2015) - Zhao, Hongwei; Chen, Jingyu; Liu, Jingjing; Han, Beizhong
<x xml:space="preserve">Abstract</x> A global regulatory network involving the response to the oxidation stress in Saccharomyces cerevisiae was revealed in this study.